The Greening of Aid: Sustainable Livelihoods in Practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Greening of Aid: Sustainable Livelihoods in Practice edited by Czech Conroy and Miles Litvinoff.